Rethinking territoriality concept on public space after pandemic COVID-19 - Sherly de Yong; Murni Rachmawati; Ima Defiana (International Journal of Public Health Science (IJPHS), 2021)
The spread and pandemic of coronavirus disease (COVID-19) that is currently happening in the world, has led to new policy steps in the security of public spaces to reduce the transmission of COVID-19 and protect public health. There is new adaptation in the policies while using space like limiting the use of public spaces, increasing social distancing between people or creating territory. Territory means specific area where are claimed or maintained (can be physically, through ruler or symbols). Territory can give a sense of security to the users. Therefore, this paper give insight and rethinking the territory concept as sense of security in interior public space and built environment where people expect to see strangers in this space. The methods in this paper are literature review method by collecting and synthesizing previous research using integrative approach. For the result is territory concept achieved as part of protection to the users in the build environment with mechanisms that should be applied in each type: the boundary between areas; limitation to the symbolic; supervision and control of space.